Group Membership Modulates Fairness Consideration Among Deaf College Students—An Event-Related Potential Study - Gong, Yuqi; Yao, Li; Chen, Xiaoyi; Xia, Qingling; Jiang, Jun; Du, Xue (Frontiers in Psychology, 2022)
Group interaction is an essential way of social interaction, and plays an important role in our social development. It has been found that when individuals participate ingroup interactions, the group identity of the interaction partner affects the subjects' mental processing and behavioral decision-making. However, little is known about how deaf college students, who are labeled distinctly different from normal hearing college students, will react when facing proposers from different groups in the Ultimatum Game(UG) and its time course. In this study, we recruited 29 deaf college students who played the UG in which they received extremely unfair, moderately unfair or fair offers from either outgroup members (normal hearing college student) or ingroup members (deaf college student), while their brain potentials were recorded. The behavioral results showed group membership did not impact the acceptance rate of deaf college students. But ERP analysis demonstrated a decreased early positivity (P2) and enhanced feedback-related negativity (FRN) elicited by ingroup members compared to the outgroup members. N1 was identified as a marginal main effect of group member, namely ingroup members is larger than outgroup members. A similar effect was identified for P3, which the outgroup members is larger than ingroup members. Our results demonstrated that group membership may moderate the performance of deaf college students in the UG. This provides some evidence for the fairness characteristics of special populations so that to improve the educational integration of colleges and universities.